Systematic review and meta-analysis of post-traumatic stress disorder as a risk factor for multiple autoimmune diseases - Mandagere, Kevin; Stoy, Savanna; Hammerle, Nathan; Zapata, Isain; Brooks, Benjamin (Frontiers in Psychiatry, 2025)
BackgroundPost Traumatic Stress Disorder (PTSD) is a prevalent and debilitating psychiatric illness that has been linked to poor health outcomes and increased risk of developing chronic health conditions, including multiple autoimmune diseases such as Systemic Lupus Erythematosus (SLE), Inflammatory Bowel Disease (IBD), Rheumatoid Arthritis (RA), and Multiple Sclerosis (MS).AimThis meta-analysis assesses the epidemiological research in this field and briefly explores the hypothesized neurobiological and immunological mechanisms that may underlie the association between PTSD and the development of Autoimmune Disease.MethodsPubMed, SCOPUS, and Cochrane Reviews databases were searched for all relevant articles in August 2023. Studies were systematically screened for relevance and inclusion criteria by two reviewers before quality assessment and data extraction were performed. Fixed and random-effect meta-analyses were performed to evaluate PTSD as a risk factor for the development of specific autoimmune diseases. Subgroup analyses examining the roles of biological sex and PTSD severity were also performed.ResultsThe initial search yielded 3010 articles where only eight prospective and retrospective cohort studies met criteria for inclusion in the meta-analysis. These eight studies were subdivided based on specific disease outcomes. Random effects model for risk of developing any autoimmune disease in persons with PTSD vs. control was 1.291 (95% CI = 1.179 to 1.412; P <0.001; n=1,984,310; 4 studies included). The strength of the association between PTSD and risk of developing specific autoimmune diseases varied by outcome condition from 1.142 (95% CI = 1.085 to 1.202, P <0.001) for risk of IBD to 1.302 (1.037 to 1.635, P = 0.023) for risk of MS. Random effects models showed statistically significant associations between PTSD and IBD, SLE, RA, MS, and Thyroiditis.ConclusionThese results suggest that the risk for developing autoimmune conditions, including SLE, MS, RA, and IBD, is significantly increased in the setting of PTSD. This association may have important implications on clinical practice and research into the pathophysiology of stress disorders.